Reading passages and conversation text in EFL textbook for junior high school: Analysis on the process of transitivity system - Lulu Farhan; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Politeknik Negeri Bali, 2023)
This research aims to identify the process types of the transitivity system from the reading passages and conversational texts of the EFL textbook entitled Modul Pengayaan for seventh-grade junior high school students, which is composed based on the implementation of Kurikulum 2013. The present study employed a descriptive qualitative research design. The data of this study are obtained from reading texts and conversational texts (text dialogues). The collected data of the transitivity process presented in sentences and clauses were analyzed using Halliday's transitivity system. The results show that all the process types of transitivity system with 35 processes were found in the reading passages and conversational texts of the textbook, namely: material process with 5 data (14.28%), mental process with 12 data (34.28%), verbal process with 3 data (8.57%), relational process with 13 data (37.14%), behavioral process with 1 data (2.85%), and existential process also with 1 data (2.85%). All the types of transitivity processes have been presented adequately based on Halliday's theory, although the two types of transitivity process (behavioral and existential process) almost have come from ignorance. Therefore, this study suggests that the textbook designer and material developer produce diverse clauses and sentences by using the six process types of transitivity in English written texts, especially in the reading passages and conversational texts.